PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL GUNA MENINGKATKAN HASIL BELAJAR SISWA KELAS VII PADA MATERI SEJARAH PROKLAMASI KEMERDEKAAN INDONESIA DI SMP LABORATORIUM STKIP KOTA JAMBI TA. 2022/2023 - Rifa’i, Ahmad; Pamungkas, Satriyo (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2023)
This study aims to improve the learning process and to improve student learning outcomes in class VII by audio-visual learning media on the history of the proclamation of Indonesian independence at STKIP Laboratory Middle School, Jambi City. The study used classroom action research (PTK) which was carried out in 2 (two) cycles, namely cycle I and cycle II. The results of the research that has been done show an increase in student learning outcomes in each cycle on the history of the proclamation of Indonesian independence after the use of audio-visual media in learning. This can be seen from the results of increasing the percentage and class average of each cycle. In cycle I, the class average score was 69 with a percentage of 60% of students who completed it, while in cycle II there was a significant increase in learning outcomes, namely with an average grade of 76 with a percentage of 100% of students who obtained completeness in learning outcomes.